2012
DOI: 10.1093/sw/swr009
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking Behaviors among Chinese Americans with Depressive Symptoms

Abstract: An exploratory survey indicated that the depression prevalence among Chinese Americans is 17.4 percent. Of 516 respondents, 34.9 percent preferred seeking advice from friends or relatives, followed by 30.2 percent not showing any preference when facing a mental health problem. Logistic regression results pointed to three contributing factors: anxiety problems, acculturation concerns, and domestic violence. Learning from these factors, the authors conducted additional analyses to connect depressive symptoms wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 35 publications
4
37
1
Order By: Relevance
“…Differences remained significant after controlling for the effects of gender and age. These results are consistent with those of previous studies that have found higher levels of negative psychological symptoms among international students from Asia or China specifically (Cross, 1995;Han et al, 2013;Leung et al, 2012;Settles et al, 2012;Yeh, 2003). Qualitative data suggested that the main sources of anxiety and stress for the Chinese students were academic factors, such as study workload and ambiguity over assessment tasks or teaching styles; life balance stressors, such as lack of time for relationships and social activities; and family stressors, including high expectations and pressure to succeed from parents.…”
Section: Discussionsupporting
confidence: 90%
“…Differences remained significant after controlling for the effects of gender and age. These results are consistent with those of previous studies that have found higher levels of negative psychological symptoms among international students from Asia or China specifically (Cross, 1995;Han et al, 2013;Leung et al, 2012;Settles et al, 2012;Yeh, 2003). Qualitative data suggested that the main sources of anxiety and stress for the Chinese students were academic factors, such as study workload and ambiguity over assessment tasks or teaching styles; life balance stressors, such as lack of time for relationships and social activities; and family stressors, including high expectations and pressure to succeed from parents.…”
Section: Discussionsupporting
confidence: 90%
“…For example, in two studies of Chinese immigrants, informal help from relatives or friends was most often preferred, followed by help from other informal sources and, finally, help from medical and mental health practitioners (39,59). In a sample of Korean immigrants and nonimmigrants, 52% preferred to go to family and friends for help with mental health problems, 40% preferred religious consultation, and 9% preferred a mental health professional (54).…”
Section: Resultsmentioning
confidence: 99%
“…In Chinese medicine, PS from shaking or an analog of earthquake is considered as a factor which impairs kidney Qi ( shen qi ) [12]. As kidney is the root of earlier heaven (the congenital constitution), it governs reproduction and development and holds oriffice of labor, whence agility and emanates.…”
Section: Introductionmentioning
confidence: 99%